Divisive Negative Discourse Biases Social Experience: A Live Experiment at a Massive Public Event - Garcia-Serrano, A (Springer Nature, 2025)
Linguistic choices, crucially including negatively valenced words and divisive messages, can bias people’s feelings, thoughts, and judgments. However, these phenomena have been typically captured with small groups in controlled settings, casting doubt on their robustness and ecological validity. Here we examined whether such effects hold in a massive public gathering. During a large TEDx event (n = 3139), participants engaged in an interactive musical game and then evaluated their perception of (active and vicarious) enjoyment and (ingroup and outgroup) performance through surveys that manipulated (a) the initial framing (‘divisive’ or ‘communal’) and (b) the questions’ valence (‘positive’, ‘neutral’, ‘negative’). Results showed that negatively valenced words reduced enjoyment and performance ratings, particularly under divisive framings. Active enjoyment also decreased under communal framings. These results were corroborated upon adjusting for sociodemographic variables. Briefly, linguistic manipulations of affect immediately altered a crowd’s perception of enjoyment and performance. These insights extend psycholinguistic models and contribute to discussions on public communication. © The Author(s) 2025.